2009
DOI: 10.1007/s11104-009-0109-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nickel concentration profiles around the roots of the hyperaccumulator plant Berkheya coddii using MRI and numerical simulations

Abstract: Investigations of soil-root interactions are hampered by the difficult experimental accessibility of the rhizosphere. Here we show the potential of Magnetic Resonance Imaging (MRI) as a non-destructive measurement technique in combination with numerical modelling to study the dynamics of the spatial distribution of dissolved nickel (Ni 2+ ) around the roots of the nickel hyperaccumulator plant Berkheya coddii. Special rhizoboxes were used in which a root monolayer had been grown, separated from an adjacent ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…23 The concentration of chelidonic acid in leaves of B. coddii is approximately 10-fold higher compared to other plant sections (Table 3) indicating that the primary location of the acid is within the leaves. Reported chelidonic acid concentrations in leaves, stems and root of non-hyperaccumulators are <200 mg kg -1 indicating that it plays a role in the hyperaccumulation process.…”
Section: Quantification Of Chelidonic Acid In B Coddiimentioning
confidence: 87%
See 1 more Smart Citation
“…23 The concentration of chelidonic acid in leaves of B. coddii is approximately 10-fold higher compared to other plant sections (Table 3) indicating that the primary location of the acid is within the leaves. Reported chelidonic acid concentrations in leaves, stems and root of non-hyperaccumulators are <200 mg kg -1 indicating that it plays a role in the hyperaccumulation process.…”
Section: Quantification Of Chelidonic Acid In B Coddiimentioning
confidence: 87%
“…21 Contradicting results were reported from studies using magnetic resonance imaging (MRI) on the roots, with results indicating a passive uptake mechanism and a specific pattern of Ni concentration at the plane of the roots. 22 Robinson et al 23 reported that the higher the content of Ni in the soil, the lower uptake of macro and micronutrients in the plant. Studies involving the effects of Ni uptake on insects were also investigated.…”
Section: Berkheya Coddiimentioning
confidence: 99%
“…With this technology, 3D acquisition can be accomplished to acquire information on plant morphology with high precision; in particular, this approach has been appreciated for imaging roots in the root zone [61]. NMR is also used for the detection of water and labeled molecule fluxes within plant organs [62][63][64].…”
Section: Magnetic Resonancementioning
confidence: 99%
“…A thinner root zone layer may also be analyzed. Our box thickness was the same as in the study by Moradi et al (2010). Thinner boxes were used for example by Whiting et al (2000) 2 cm, Rudolph et al (2012) 0.5 cm, and Youssef and Chino (1988) 1 mm.…”
Section: Mathematical Modeling Of Root Water Uptakementioning
confidence: 99%
“…thickness, transparency etc. ), roots can be either directly photographed or the neutron, x-ray computed tomography, NMR, 2D light transition imaging technique can be applied (de Dorlodot et al, 2007;Doussan et al, 2006;Garrigues et al, 2006;Moradi et al, 2009Moradi et al, , 2010Moradi et al, , 2013Moran et al, 2000;Oswald et al, 2008;Rudolph et al, 2012Rudolph et al, , 2013Rudolph-Mohr et al, 2014;Stingaciu et al, 2013). These techniques were mostly applied to analyze root development in the early stage of plant and roots growth.…”
Section: Introductionmentioning
confidence: 99%